Aeschylus Agamemnon 104–05, Homer and the Epic Tradition: A New Survey. (28th November 2018) - Rodighiero, Andrea
Abstract: This article is a discussion and analysis of Aeschylus Agamemnon 104–05, with special reference to the epic models operating behind the typically Homeric enjambement ἀνδρῶν / ἐκτελέων. The ἄνδρες should be understood as the Argive heroes of the expedition against Troy, and not as the sons of Atreus, Agamemnon and Menelaus. This interpretation is supported by a number of examples taken from Archaic and Hellenistic epic poems.